(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Alloploid hybrids of Nepeta L. (allotriploid, pentaploid and hexaploid) are obtained by means of hybridization of three spesies: N. transcaucasica, N. grandiflora and N. cataria. Scheme of hybridization is given as well.